ADSORPTION OF RHODAMINE B USING K-KARAGENAN/PVA/FE3O4 ADSORBENT - Arman, Etriyanto
Rhodamine B is a widely used dye in the textile industry. The use of rhodamine B will lead to increase waste pollutant in environment, especially in waters that have the potential to become pollutants. Adsorption is an effective method for reducing pollutants such as dyes from liquid waste because the process is easy, relatively inexpensive with high effectiveness. In this study, an adsorbent was made in the form of ?–carrageenan/PVA/Fe3O4 adsorbent for rhodamine B adsorption. The adsorbent were characterized using several instruments, such as Fourier Transform Infrared Spectroscopy (FTIR), X-ray diffraction (XRD), Scanning Electron Microscopy (SEM), and DelsaTM Nano C Particle Analyzer. The results of characterization by FTIR showed typical absorption bands of a number of functional groups found in ?–carrageenan, PVA and magnetite (Fe3O4). The adsorbent diffractogram shows a typical pattern of Fe3O4 magnetite at a diffraction angle value of 30.2?; 35.5?; 43.5?; 53.4?; 57.4?; and 63.5?. SEM image shows the surface of the adsorbent is corrugated and porous. ?–carrageenan/PVA/Fe3O4 adsorbent have an average diameter of 1.46 mm. The optimum adsorption parameters to adsorb rhodamine B were achieved at pH 2, and contact time of 120 minutes using the batch method. The adsorption process of rhodamine B followed the pseudo-second-order reaction kinetics model and the Langmuir isotherm model with a maximum adsorption capacity of 201.47 mg/g. The adsorption of rhodamine B is exothermic, with an increase in the entropy of the system and is spontaneous, with a value of ?H = -2.52 kJ/mol and ?S = 0.09 kJ/mol.K. ?–carrageenan /PVA/Fe3O4 adsorbent have good repeatability, seen from the adsorption-desorption capacity for 3 cycles using 0.5 M KCl dissolved in a mixture of ethanol water with a ratio of 50:50 (V/V) as a desorption solution.